Establishment and application of a fluorescence-based nucleic acid detection system for canine parvovirus - Weng, Shaoting; Cui, Yuelong; Ma, Shengming; Lian, Kaiqi; Zhang, Mingliang; Wang, Liqiang; Dou, Xuekun; Huang, Rong; Zhang, Longfei; Wang, Yao (Frontiers in Veterinary Science, 2025)
Canine Parvovirus (CPV) is a significant pathogen threatening the health of canine worldwide, characterized by high infectivity and fatality rates. A rapid, accurate, and convenient detection method is crucial for early intervention and control of CPV infections. In this study, a novel visual detection method for CPV based on nucleic acid mismatch endonuclease detection (NMED) was established. This method amplifies the conserved region of the CPV VP2 gene through optimized recombinase polymerase amplification (RPA). Subsequently, the amplified products are hybridized with specially designed fluorescently labeled probes. Then, T7 endonuclease I (T7E I) specifically recognizes and cleaves the hybridized products. Finally, the detection signals are visually interpreted using colloidal gold lateral flow assay (LFA). The results of our study indicate that the NMED method can complete DNA sample analysis within 50 min, with strong specificity and no cross - reactions with other common canine viruses. Sensitivity tests show that its detection limit is above 10 copies/μL. In the validation of 35 clinically suspected samples, the overall coincidence rate with RPA and qPCR is over 97.14%, and it reaches 100% in strongly positive samples. In conclusion, this study has established an efficient, specific, and visual nucleic acid detection method for CPV. Its establishment provides an important technical support for the early warning and precise prevention and control of CPV infections.